Bio-based epoxy thermosets with rosin derived imidoamine curing agents and their structure-property relationships - T. Thakur; S. Jaswal; S. Parihar; B. Gaur; A. S. Singha (eXPRESS Polymer Letters, 2020)
Multifunctional bio-based epoxy resin (PEMPAE) was synthesized by reacting Diels-Alder adduct of gum rosin and maleic anhydride (MPA) with pentaerythritol to get the esterified product (PEMPA) which was further epoxidized using epichlorohydrin and potassium hydroxide. This paper includes the synthesis of bio-based imidoamine curing agent (IAEDK) by reacting diamino diphenyl ether (DDE) with dimaleopimaryl ketone (DMPK), a dehydrodecarboxylated derivative of MPA. The synthesized products were characterized by Fourier transform infrared Spectroscopy (FTIR), proton and 13C nuclear magnetic resonance spectroscopy (1H-NMR and 13C-NMR). Curing dynamics of rosin-based epoxy cured with rosinbased imidoamine crosslinker were evaluated using differential scanning calorimetry (DSC) and were compared with resin cured with synthesized DMPK and commercial DDE curing agents. The mechanical properties and thermal stability of the cured epoxy samples were evaluated using a universal testing machine (UTM) and thermogravimetric analyzer (TGA), respectively. The chemical resistance of the samples was determined in terms of % weight loss when immersed in NaOH, HCl and NaCl solutions. The morphological changes were also evaluated via scanning electron microscopy (SEM). Results revealed that rosin-based epoxy cured with imidoamine curing agent gave preeminent properties over the commercial one. The studies suggested that curing properties were greatly affected by the molecular topology and kind of curing agent used.